The Value of Soil Knowledge in Understanding Wine Terroir - White, Robert E. (Frontiers in Environmental Science, 2020)
There is an extensive literature on the role of soil physicochemical factors such as rate of water supply, N supply and soil temperature in wine terroir expression, especially for dry-grown vines. Other recent literature invokes the possibility of unique strains of the natural yeast Saccharomyces cerevisiae influencing must fermentations to produce distinctive aroma profiles in wines. Others suggest that the composition of the soil microbiome at particular sites can influence vine growth, fruit composition and wine characteristics to create a microbial terroir. Because terroir is a multifactor concept, no general quantitative relationships between one or more soil properties and the distinctive characteristics of wine from a particular site have been identified; rather a unique combination of soil factor values interacts with local climate, grape variety, vintage, canopy management, and winemaker technique to determine a site’s terroir. However, with modern methods of sensing spatially referenced values of environmental and other variables at high resolution, terroirs can be mapped. This provides a platform for monitoring terroirs over time and recording how they respond to changes in environmental factors or to manipulations in the vineyard and winery.